Vindija Cave and the Modern Human Peopling of Europe - Janković, Ivor; Karavanić, Ivor; Ahern, James C. M.; Brajković, Dejana Mauch Lenardić, Jadranka; Smith, Fred H. (2006)
Vindija cave in Croatia has yielded the youngest securely dated Neandertal skeletal remains in Central/Eastern Europe. In addition, these remains have been found in association with archaeological material exhibiting Upper Paleolithic elements. Due to its geographic location and date, the Vindija remains are particularly crucial for the understanding of initial modern human peopling of Europe and the nature of the Neandertal demise. The significance of archaeological and paleontological finds and hominin fossils from this site is discussed in the light of new finds at Vindija and recent developments in the fields of paleoanthropology and prehistoric archaeology. Furthermore, the impact of revised chronology for several crucial specimens and sites throughout Europe, including Vindija, is discussed.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG